Panorama conceptual y antecedentes de los sistemas de información en salud (Colombia Medica, 1993)
In spite of the advances related to the technology of communi-cations and information sciences, in Colombia as in most of the underdeveloped countries, data available on health and related matters remain insufficient, poorly coordinated and of dubious quality. A Health Infonnation Sy$tem (HIS) has 2 uses of prime importance: for detennining the health services that should be offered to the community, and to serve as a basis for financial decisions. The HIS has 4 components, all of them closely related: a register of vital statistics, a system for epidemiologic surveillance, a system for managerial moni-toring and evaluation, and a well defined network of providers and users of information. _ The key issue in developing a IIlS is that all participants must be involved in its planning and operation, in order to make the system functional and to guarantee its proper use. The opportunity for improving the HIS in Colombia has been opened by the emphasis given to the local health systems (SILOS), in which the community is involved in the planning stage, and consequently the devel-opment ofhealth indicators is not merely an academic exercise, but a creative process, based on the community aims and goals or, in other words, a realistic exercise.